2005
DOI: 10.1097/01.ccm.0000186761.41090.c6
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnic acidosis does not modulate the severity of bacterial pneumonia–induced lung injury

Abstract: We conclude that hypercapnic acidosis did not alter the magnitude of the lung injury induced by intratracheal E. coli instillation in the presence or absence of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 42 publications
0
47
1
Order By: Relevance
“…By contrast, studies on the effects of hypercapnia during bacterial pulmonary infection in rats have produced highly variable results (17)(18)(19)(20)(21). In those reports, lung injury parameters and bacterial burden, as assessed in anesthetized and mechanically ventilated animals after intratracheal inoculation with Escherichia coli, were variously unaffected, worsened, or attenuated by hypercapnia.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…By contrast, studies on the effects of hypercapnia during bacterial pulmonary infection in rats have produced highly variable results (17)(18)(19)(20)(21). In those reports, lung injury parameters and bacterial burden, as assessed in anesthetized and mechanically ventilated animals after intratracheal inoculation with Escherichia coli, were variously unaffected, worsened, or attenuated by hypercapnia.…”
mentioning
confidence: 87%
“…As already noted, another group has studied the impact of hypercapnia in a rat model of pulmonary infection with E. coli, finding alternately deleterious or beneficial effects using a variety of protocols in multiple reports (17)(18)(19)(20)(21). In all but one of these, the effects of hypercapnia were evaluated exclusively in anesthetized animals undergoing mechanical ventilation over a period of 4 to 6 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Immediately postmortem, the heart-lung block was removed and bronchoalveolar lavage (BAL) carried out. 23,24 BAL differential cell counts were performed. BAL protein was measured using a Micro BCA TM Protein assay kit (Pierce, Rockford, IL).…”
Section: Lung Injury and Repair Assessmentmentioning
confidence: 99%
“…27 The left lung was fixed using paraformaldehyde, and histologic lung injury assessed using quantitative stereology. 23,27 The investigator performing the physiologic assessment was not blinded to group allocation; however, the investigators were blinded for all other assessments and assays. …”
mentioning
confidence: 99%
“…Intriguingly, these protective eff ects were mediated by a mechanism indepen dent of neutrophil function. In contrast, hypercapnic acidosis did not alter the magnitude of lung injury in a less severe acute bacterial pneumonia [39]. Importantly these in vivo studies showed no increase in bacterial count in animals exposed to hypercapnic acidosis, a reassuring fi nding given concerns regarding retardation of the host bactericidal response and potential bacterial proliferation.…”
Section: Early Lung Infectionmentioning
confidence: 73%